PERBUATAN MELAWAN HUKUM LINGKUNGAN PENAFSIRAN EKSTENSIF DAN DOKTRIN INJURIA SINE DAMNO - Shidarta Shidarta (Komisi Yudisial RI, 2010)
ABSTRACTTort is a legal instrument that provides remedies for civil wrongdoings not arising out of contracts. A plantiff who suffers damage may use this instrument to file a lawsuit based on Article 1365 of Civil Code. According to this article, the plantiff is the person who should prove the wrongdoing, damage, and other elements of tort. Such a burden of proof is not in line with the spirit of strict liability as stipulated in Article 35 of Law No. 23 Year 1997. Unlike civil cases in general, the terms of wrongdoing and damage of tort could be defined broadly in environmental legal cases. For instance, a damage does not necessarily mean a physical injury.. Judges are very much anticipated to interpret such elements extensively rather than restrictively. Court Verdict Number 548/Pdt.G/2007/PN.JAK.SEL studied here seems to take a different direction from that of wideranging interpretation. Through this analysis the author resolves that imposing the doctrine of ‘injuria sine damno’ in some extent shall broaden the meanings of some crucial elements of tort.Keywords: tort, injuria sine damno, environmental law. ABSTRAKPerbuatan melawan hukum adalah sarana yang disediakan untuk mengatasi pelanggaran kontrak dalam hukum perdata. Penggugat yang menderita kergian dapat memakai instrumen ini untuk menggugat atas dasar Pasal 1365 KUH Perdata. Pasal ini menyatakan bahwa si penggugatlah yang harus membuktikan kesalahan, kerugian, dan unsur-unsur lain dari perbuatan melawan hukum itu. Beban pembuktian ini tidak sejalan dengan semangat tanggung jawab mutlak yang ditetapkan dalam Pasal 35 UU No. 23 Tahun 1997. Tidak seperti kasus-kasus perdata pada umumnya, istilah kerugian tidaklah harus bermakna kerugian fisik. Hakim tampaknya lebih menafsirkan unsur-unsur perbuatan melawan hukum ini lebih luas daripada mempersempitnya. Putusan hakim NO. 548/Pdt.G/2007/PN.JAK.SEL yang ditelaah di sini menunjukkan arah yang berbeda daripada penafsiran memperluas. Melalui analisisnya, penulis artikel ini menyarankanagar doktrin ‘injuria sine damno’ yang digunakan dalam hal unsur-unsur penting dalam perbuatan melwan hukum itu harus ditafsirkan secara lebih luas.Kata kunci: perbuatan melawan hukum, injuria sine damno, hukum lingkungan.